STABILITAS KANDUNGAN AMILOSA BERAS BEBERAPA VARITAS PADI SAWAH DI SUMATERA BARAT - Anhar, Azwir (Sainstek : Jurnal Sains dan Teknologi, 2011)
Amylose content of rice is one of the variables that determine the quality of rice. Although Solok considered a first-class rice-producing areas inWest Sumatra, but a stable varieties will produce amylose content is relatively similar across all planting sites, so it can be cultivated in various regions. The study was conducted at 3 locations lowland rice production centers inWest Sumaterathat is Solok, Bukittiggi and Pariaman. The research design used at each location is randomized block design with 3 replications. The treatment consisted of 5 varieties of rice that is Cisokan, Anak daro, Randah-kuniang, Kuriak kusuik and Saratuih hari. The results showed that the five varieties tested showed a stable amylose content.Key words: stability, amylose, rice, west sumatera